Pengaruh Penerapan Sistem Akuntansi Pemerintahan dan Sistem Pengendalian Intern Pemerintah terhadap Kualitas Laporan Keuangan - Siti Fatimah; Lili Indrawati (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
With the implementation of Government Regulation No. 71 of 2010 concerning Government Accounting System and Government Regulation No. 60 of 2008 concerning the Government's Internal Control System requires local governments to implement a Government Accounting System and Government Internal Control System as a form of accountability for the financial and security of regional assets. This study aims to determine the effect of the application of the Government Accounting System and Government Internal Control System on the quality of financial reports in several agencies in Bandung Regency through a causal associative approach. This research is a quantitative research with primary data obtained from the results of questionnaires distributed to 37 respondents. The sample used in this study consisted of 8 agencies that manage income and expenditure in Bandung Regency. The data analysis technique in this study is multiple regression analysis using IBM SPSS 26. The results showed that the implementation of the Government Accounting System had a positive effect on the quality of financial reports, the Government's Internal Control System had no positive effect on the quality of financial reports, and the Government Accounting System and the Government's Internal Control System simultaneously had a positive effect on the quality of financial reports.